Equine rhinitis B viruses in horse fecal samples from the Middle East. Issue 1 (December 2016) - Woo, Patrick; Lau, Susanna; Choi, Garnet; Huang, Yi; Wernery, Renate; Joseph, Sunitha; Wong, Emily; Elizabeth, Shyna; Patteril, Nissy; Li, Tong; Wernery, Ulrich; Yuen, Kwok-Yung
Abstract Background Among all known picornaviruses, only two species, equine rhinitis A virus and equine rhinitis B virus (ERBV) are known to infect horses, causing respiratory infections. No reports have described the detection of ERBV in fecal samples of horses and no complete genome sequences of ERBV3 are available. Methods We performed a molecular epidemiology study to detect ERBVs in horses from Dubai and Hong Kong. Complete genome sequencing of the ERBVs as well as viral loads and genome, phylogenetic and evolutionary analysis were performed on the positive samples. Results ERBV was detected in four (13.8 %) of the 29 fecal samples in horses from Dubai, with viral loads 8.28 × 103 to 5.83 × 104 copies per ml, but none of the 47 fecal samples in horses from Hong Kong by RT-PCR. Complete genome sequencing and phylogenetic analysis showed that three of the four strains were ERBV3 and one was ERBV2. The major difference between the genomes of ERBV3 and those of ERBV1 and ERBV2 lied in the amino acid sequences of their VP1 proteins. The Ka/Ks ratios of all the coding regions in the ERBV3 genomes were all <0.1, suggesting that ERBV3 were stably evolving in horses. Using the uncorrelated lognormal distributed relaxed clock model on VP1 gene, the date of the most recent common ancestor (MRCA) of ERBV3 was estimated to be 1785 (HPDs, 1176 to 1937) and the MRCA dates of ERBV1 and ERBV2 were estimated to be 1848 (HPDs, 1466 to 1949) respectively. Conclusions Both acid stable (ERBV3) and acid labile (ERBV2) ERBVs could be found in fecal samples of horses. Detection of ERBVs in fecal samples would have implications for their transmission and potential role in gastrointestinal diseases as well as fecal sampling as an alternative method of identifying infected horses.